Neoadjuvant chemotherapy combined with transoral robotic surgery for stage III and IV laryngeal and hypopharyngeal carcinomas. (May 2023) - Sampieri, Claudio; Costantino, Andrea; Pirola, Francesca; Kim, Dahee; Lee, Kyuin; Kim, Se-Heon
Highlights: Advanced laryngeal cancer can be treated conservatively with TORS coupled with NAC. NAC can help to select tumors for adjuvant treatment based on pathological response. NAC followed by TORS can enhance the prognosis while providing organ preservation. Abstract: Objectives: To analyze the oncological and functional outcomes of patients with stage III-IV laryngo-hypopharyngeal cancer who underwent neoadjuvant chemotherapy (NAC) with subsequent transoral robotic surgery (TORS). Materials and methods: A single-center retrospective cohort study included a total of 100 patients (median age of 67.0) affected by stage III-IV supraglottic or hypopharyngeal cancer. All patients underwent NAC followed by TORS and risk-adjusted adjuvant therapy. The primary outcome was recurrence-free survival (RFS). Results: The median follow-up time was 24.0 months. Estimated 2-year (95% CI) OS, DSS, and RFS were 75% (66% − 85%), 84% (76% − 92%), and 65% (56% – 76%), respectively. Among the 11 patients who relapsed on the primary site, 3 underwent salvage total laryngectomy, 3 underwent salvage CRT, and the others receive palliation or supportive care. At 6 months from surgery, 17 patients were still tracheostomized or had a stoma retainer, while 15 were gastrostomy dependent. At the Cox multivariable analysis, the clinical stage at presentation, the number of NAC cycles, and the presence of LVI were found to be independently correlated with the RFS. Conclusion: This study demonstrates that NAC followed by TORS can obtain good tumor control, survival, and organ preservation rates in stage III-IV laryngo-hypopharyngeal cancer.